2020
DOI: 10.3892/ol.2020.11688
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-mediated IARS2 knockdown inhibits proliferation and promotes apoptosis in human melanoma A375 cells

Abstract: IARS2, which encodes the mitochondrial form of isoleucyl-tRNA synthetase, has been found to play an important role in a range of diseases, including cancer. However, the relationship between IARS2 and melanoma is still unclear. To evaluate the role of IARS2 in melanoma, we constructed a stable A375 cell line with IARS2 knockdown via lentivirus-mediated small interfering RNAs. The expression of IARS2 was measured by real time-quantitative Polymerase Chain Reaction and western blot analysis. Cell counting, 3-(4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The present study was, to the best of our knowledge, the first to demonstrate that IARS2 knockdown inhibited cell proliferation and promoted the apoptosis of human OS cells, which is consistent with previous studies on the role in IARS2 in other tumor types ( 19 21 ). In the present study, the expression of IARS2, and its relationship with overall and disease-free survival were analyzed using the GEPIA2 database.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study was, to the best of our knowledge, the first to demonstrate that IARS2 knockdown inhibited cell proliferation and promoted the apoptosis of human OS cells, which is consistent with previous studies on the role in IARS2 in other tumor types ( 19 21 ). In the present study, the expression of IARS2, and its relationship with overall and disease-free survival were analyzed using the GEPIA2 database.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, whether these signaling pathways are also involved in OS cell proliferation and apoptosis driven by IARS2 should be analyzed in future research. Furthermore, due to the normal sample limitation in the GEPIA2 dataset and previous study has not reported an association between survival and IARS2 expression so far ( 19 21 ), the expression and survival curve should be further confirmed with more healthy and OS clinical samples. In addition, the expression of IARS2 in tumor and tumor-adjacent tissue needs to be detected by western blotting and immunohistochemistry.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…IARS2 mainly catalyzes tRNA aminoacylation and correlates with malignant proliferation and apoptosis resistance of tumor cells. In non-small cell lung cancer, gastric cancer, melanoma and acute myeloid leukemia, knockout of IARS2 inhibits cell proliferation and promotes apoptosis 36 39 . PRCC is an important element involved in the formation of the spliceosome 40 .…”
Section: Discussionmentioning
confidence: 99%
“…IARS2 is a ubiquitously expressed mitochondrial tRNA synthase that catalyses the aminoacylation of tRNA with isoleucine. Knockdown of IARS2 has been shown to promote apoptosis and inhibit proliferation in melanoma cells ( Ma et al, 2020 ). NEK4 is a serine/threonine kinase involved in replicative senescence and for normal cell cycle arrest in response to double-stranded DNA damage ( Nguyen et al, 2012 ).…”
Section: Human Hyaluronidase 4 Protein Expression and Structurementioning
confidence: 99%